Space Use and the Physical Attributes of Acute Care Units: A Quantitative Study. (January 2022) - Kelly, David; Pingel, Michael J.
: This article shares the results of a quantitative analysis of the space use and physical attributes of 140 acute care units (ACU) completed since 2007. Objective: To fill a gap in the literature with respect to the state of practice for ACU design over the study period by investigating relationships among the physical characteristics and density of completed ACUs. Background: Robust industry interest about the topic—further agitated by the dearth of large-scale quantitative research regarding ACU space use—motivated completion of the study. Method: Through extraordinary collaboration by participating firms, floor plans of 140 new ACUs from the study period were gathered, systematically measured, and then analyzed. Results: Structural bay size, nurse station location, and the number of beds per unit were found to have significant relationships to ACU floor-gross area per bed. Additionally, nine significant associations among the explanatory variables were found, including moderate relationships among bay size, nurse station location, room handedness, and toilet room placement. Conclusion: The results suggest that project design teams tend to bundle key physical attributes together when planning ACUs. Moreover, density increases resulting from bay size reduction diminish as the bay size drops below 31′. Any impacts resulting from the major external events demarking the last decade were not sufficient to appreciably affect ACU density. Lastly, those concerned with increasing density and controlling ACU floor gross area are alerted to explore design options featuring bay sizes of approximately 30′ in conjunction with a centralized nursing model containing more than 32 beds per unit.